1988
DOI: 10.1016/0014-5793(88)80804-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fructose 2,6‐bisphosphate levels in cold‐acclimated brown adipose tissue of rat

Abstract: The effects of cold exposure and "14 administration on fructose 2,6-bisphosphate levels, phosphofructokinase-2 and pyruvate kinase activities were examined in rat brown adipose tissue. Cold adaptation (14 days) gave rise to a 2-fold increase in the amount of fructose 2,6-bisphosphate and phosphofructokinase-2 activity, and increased the pyruvate kinase activity 4-fold. If, in addition, the cold-acclimated rats were treated with I"4, these parameters were again significantly enhanced. The effect on phosphofruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Other Enzymatic Assays. Lactate dehydrogenase (LDH) and pyruvate kinase (PK) were measured by standard procedures in the 12,000 g supernatant of Jurkat T cell homogenate as described previously (22). Hexokinase (HK) was measured in the homogenate of Jurkat T cells as reported elsewhere (23).…”
Section: Methodsmentioning
confidence: 99%
“…Other Enzymatic Assays. Lactate dehydrogenase (LDH) and pyruvate kinase (PK) were measured by standard procedures in the 12,000 g supernatant of Jurkat T cell homogenate as described previously (22). Hexokinase (HK) was measured in the homogenate of Jurkat T cells as reported elsewhere (23).…”
Section: Methodsmentioning
confidence: 99%
“…Methionine sulfoxide, fructose 2,6-bisphosphate (Sobrino et al, 1988), cyclic guanosine monophosphate (cGMP) (Hoffmann et al, 2015), and pantothenic acid (vitamin B5) levels in serum were significantly higher in control mice at both 22 C and 4 C compared to ABX individuals. In contrast, 11b-prostaglandin F2awas significantly lower in control mice at both 22 C and 4 C. A previous study reported that the gut microbiota may regulate tryptophan metabolism through tryptophan hydroxylase and promote serotonin biosynthesis (Yano et al, 2015).…”
Section: Gut Microbiota Depletion Damages Thermoregulationmentioning
confidence: 99%
“…There are several isoforms of PK, including two muscle isoforms: muscle pyruvate kinase 1 and 2 ( Pkm1 and Pkm2 ). Studies with rodents have demonstrated a cold-induced increase in activity of HK, PFK and PK in BAT 911 . Consistent with this, we have reported increased expression of many glycolytic enzymes in BAT from cold-exposed mice 8 .…”
Section: Introductionmentioning
confidence: 99%